Home‐based delivery of variable length prolonged exposure therapy: A comparison of clinical efficacy between service modalities. Issue 4 (24th December 2019) - Morland, Leslie A.; Mackintosh, Margaret‐Anne; Glassman, Lisa H.; Wells, Stephanie Y.; Thorp, Steven R.; Rauch, Sheila A. M.; Cunningham, Phillippe B.; Tuerk, Peter W.; Grubbs, Kathleen M.; Golshan, Shahrokh; Sohn, Min Ji; Acierno, Ron
Abstract: Objective: This study examined clinical and retention outcomes following variable length prolonged exposure (PE) for posttraumatic stress disorder (PTSD) delivered by one of three treatment modalities (i.e., home‐based telehealth [HBT], office‐based telehealth [OBT], or in‐home‐in‐person [IHIP]). Method: A randomized clinical trial design was used to compare variable‐length PE delivered through HBT, OBT, or IHIP. Treatment duration (i.e., number of sessions) was determined by either achievement of a criterion score on the PTSD Checklist for Diagnostic and Statistical Manual‐5 ( DSM‐5 ; PTSD Checklist for DSM‐5 ) for two consecutive sessions or completion of 15 sessions. Participants received PE via HBT ( n  = 58), OBT ( n  = 59) or IHIP ( n  = 58). Data were collected between 2012 and 2018, and PTSD was diagnosed using the Clinician‐Administered PTSD Scale for DSM‐5 (CAPS‐5), administered at baseline, posttreatment, and 6 months following treatment completion. The primary clinical outcome was CAPS‐5 PTSD severity. Secondary outcomes included self‐reported PTSD and depression symptoms, as well as treatment dropout. Results: The clinical effectiveness of PE did not differ by treatment modality across any time point; however, there was a significant difference in treatment dropout. Veterans in the HBT (odds ratio [OR] = 2.67; 95% confidence interval [CI] = 1.10, 6.52; p  = .031) and OBT (OR = 5.08; 95% CI = 2.10; 12.26; p  < .001) conditions were significantly more likely than veterans in IHIP to drop out of treatment. Conclusions: Providers can effectively deliver PE through telehealth and in‐home, in‐person modalities although the rate of treatment completion was higher in IHIP care.